PENERAPAN MODEL PBL TERHADAP PENINGKATAN PENGUASAAN KONSEP PESERTA DIDIK SMA YPPK TERUNA BAKTI JAYAPURA - Syukur, Siti Marwah; Triwiyono, Triwiyono; Lasmono, Paulus G. D. (Universitas Cenderawasih, 2024)
This study aims to determine the increase in mastery of students' concepts on the subject of mechanical waves. This study uses the quasi experimental design and experimental design method that is used is the Non-equivalent Control Groups Design involving two study groups, the experimental and control classes, which were carried out at the SMA YPPK Teruna Bakti Jayapura in the semester 2018/2019. The number of samples in the research class, namely the experimental class and control class, each numbered 33 students. The sampling technique used was nonprobability sampling using purposive sampling. The instrument of data collection used is a test to see the increase in mastery of students' concepts through the pretest and posttest. To find out the increase in mastery of students' concepts used N-Gain analysis. Whereas to see the difference in mastery of participants' concepts taught with PBL learning models and students taught with conventional learning models used different statistical analysis tests. The results showed that there were significant differences in mastery of concepts between students who were taught with PBL learning models and students taught with conventional learning models for all mechanical wave concepts which were shown at a significance value of a <0.05 which was 0,000.